Environmental Liability in Ukraine and the EU - Ladychenko, Viktor; Yara, Olena; Uliutina, Olena; Golovko, Liudmyla (European Journal of Sustainable Development, 2019)
This scholarly work examines the environmental protection legislation of Ukraine and its application in practice, aiming to identify the main challenges it faces in the context of the required harmonization of Ukrainian environmental legislation with EU law according to the Association Agreement, while also making suggestions on how to better respond to these issues. This paper also refers to the experience of EU member states in the field of environmental liability. Legal nature, content and meaning of the criminal liability of legal persons in the environmental sphere according to the law of EU member states were studied in order to determine the appropriateness and mechanism of implementation of such responsibility in Ukraine. Arguments for establishment of criminal liability of legal persons were presented. Keywords: Environmental policy, environmental crime, environmental responsibility, adaptation of Ukrainian environmental legislation to EU standards.